How Nanofibers Carry the Load: Toward a Universal and Reliable Approach for Tensile Testing of Polymeric Nanofibrous Membranes. Issue 7 (24th May 2021) - Maccaferri, Emanuele; Cocchi, Davide; Mazzocchetti, Laura; Benelli, Tiziana; Brugo, Tommaso Maria; Giorgini, Loris; Zucchelli, Andrea
Abstract: Nanofibrous nonwovens show high versatility and outstanding properties, with reduced weight. Porous morphology, high material flexibility and deformability challenge their mechanical testing, severely affecting results reliability. Still today, a specific technical standard method to carry out tensile testing of nonwoven nanofibrous mats is lacking, as well as studies concerning tensile test data reliability. In this work, an accurate, systematic, and critical study is presented concerning tensile testing of nonwovens, using electrospun Nylon 66 random nanofibrous mats as a case study. Nanofibers diameter and specimen geometry are investigated to thoroughly describe the nanomat tensile behavior, also considering the polymer thermal properties, and the nanofibers crossings number as a function of the nanofibers diameter. Below a threshold value, which lies between 150 and 250 nm, the overall mat mechanical behavior changes from ductile to brittle, showing enhanced elastic modulus for a high number of nanofibers crossings. While specimen geometry does not affect tensile results. Stress–strain data are analyzed using a phenomenological data fitting model to better interpret the tensile behavior. The experimental results demonstrate the high reliability of the proposed mass‐based load normalization, providing a simple, effective, and universally suitable method for obtaining high reproducible tensile stress–strain curves. Abstract : Mechanical properties assessment of nanofibrous nonwovens is complex due to their porous morphology and soft nature, possibly leading to inaccurate results. Here, the high reliability of mass‐based normalization of load with respect to the cross‐section is proposed and demonstrated using Nylon 66 nanofibers, providing a simple, effective, and universally suitable method for obtaining high reproducible tensile stress–strain curves.